2000
DOI: 10.1002/1097-461x(2000)80:3<439::aid-qua14>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Density functional investigation of atmospheric sulfur chemistry. I. Enthalpy of formation of HSO and related molecules

Abstract: The enthalpy of formation of several species intervening in the atmospheric chemistry of sulfur compounds (SH, H2S, SO, HSO, SOH) have been calculated using density functional theory with correlation consistent basis sets and extrapolation to the complete basis set limit. Excellent agreement with experiment is found for the species of which the enthalpy of formation are well determined. The values predicted for HSO [ΔfH°298K(HSO)=−27.8±2.1 kJ/mol] and SOH [ΔfH°298K(SOH)=−6.8±2.1 kJ/mol] agree well with previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 48 publications
(99 reference statements)
5
69
0
Order By: Relevance
“…However, the preference for HSO is correctly predicted with the large 6-311++G(3df,3pd) basis set. This behavior with the increasing size of the basis set has been observed previously using higher-level ab initio methods in combination with extended basis sets and extrapolations to the CBS limit [11,17,19,20]. Thus, the DE e and DE 0 energy differences at the B3LYP/6-311++G(3df,3pd) level (2.75 and 4.50 kcal/ mol, respectively) are in reasonable agreement with the values obtained employing much more expensive calculations as B3LYP/aug-cc-pV(5+d)Z (3.23 and 4.98 kcal/mol) [20], CASSCF + 1 + 2/cc-pV5Z (2.60 and 4.20 kcal/mol) [11] and CCSD(T)/CBS limit (2.40 and 4.20 kcal/mol) [19].…”
Section: Equilibrium Geometries and Isomer Preferencessupporting
confidence: 79%
See 3 more Smart Citations
“…However, the preference for HSO is correctly predicted with the large 6-311++G(3df,3pd) basis set. This behavior with the increasing size of the basis set has been observed previously using higher-level ab initio methods in combination with extended basis sets and extrapolations to the CBS limit [11,17,19,20]. Thus, the DE e and DE 0 energy differences at the B3LYP/6-311++G(3df,3pd) level (2.75 and 4.50 kcal/ mol, respectively) are in reasonable agreement with the values obtained employing much more expensive calculations as B3LYP/aug-cc-pV(5+d)Z (3.23 and 4.98 kcal/mol) [20], CASSCF + 1 + 2/cc-pV5Z (2.60 and 4.20 kcal/mol) [11] and CCSD(T)/CBS limit (2.40 and 4.20 kcal/mol) [19].…”
Section: Equilibrium Geometries and Isomer Preferencessupporting
confidence: 79%
“…However, after the work of Xantheas and Dunning [10,11] with multireference methods and correlation consistent basis sets of up to quintuple-f quality, it seems well-established that HSO is more stable than SOH. Further theoretical investigations of Espinosa [12], Essefar [13], Wilson [14], Goumri [15], Decker [16], Denis et al [17,18] and Wilson et al [19,20] confirmed the preference of the HSO isomer.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The HO 2 [1][2][3] and HOS/SOH [4][5][6][7] radicals are interesting to computational chemists due to their importance in various chemical processes, especially processes in the atmosphere. The present work reports theoretical calculations for a triatomic molecule of analogous electronic structure, TeOH.…”
Section: Introductionmentioning
confidence: 99%